2007
DOI: 10.4067/s0716-078x2007000100006
|View full text |Cite
|
Sign up to set email alerts
|

Marine diatoms from Buenos Aires coastal waters (Argentina): II. Thalassionemataceae and Rhaphoneidaceae

Abstract: This study describes the diversity of the species belonging to the diatom families Thalassionemataceae Round and Rhaphoneidaceae Forti frequently found in the temperate marine coastal waters of Buenos Aires Province, Argentina, from October 1994 to September 2000. It comprises morphological, taxonomic and distributional analysis of species found in planktonic samples collected at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 5 publications
0
18
0
7
Order By: Relevance
“…Once these small diatoms have been reliably described, their identifi cation during routine plankton surveys will be greatly improved and increase the resolution of ecologically oriented projects. To the south of our study area, T. mala and T. minuscula were already reported in Argentinean waters, reaching high density in late winter and early spring (Gayoso 1989;Ferrario & Sar 1988;Sar et al 2001;2002;Vouilloud 2003). In our material from Paraná state, these species were abundant in late spring, when they comprised the main phytoplankton biomass.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Once these small diatoms have been reliably described, their identifi cation during routine plankton surveys will be greatly improved and increase the resolution of ecologically oriented projects. To the south of our study area, T. mala and T. minuscula were already reported in Argentinean waters, reaching high density in late winter and early spring (Gayoso 1989;Ferrario & Sar 1988;Sar et al 2001;2002;Vouilloud 2003). In our material from Paraná state, these species were abundant in late spring, when they comprised the main phytoplankton biomass.…”
Section: Discussionmentioning
confidence: 65%
“…Geographic distribution: Brazil (Rio Grande do Sul, Garcia & Odebrecht 2009a; Baía de Guaratuba, Paraná, Lehmkuhl et al 2010); Argentina (Ferrario & Galván 1989); Province of Chubut (Ferrario & Sar 1988); Balneario Las Grutas (Sar 1996); Balnearios Santa Teresita, Mar de Ajó, Nueva Atlantis, Pinamar and Villa Gesel -Buenos Aires (Sar et al 2001); Gulf of San Matías (Sar et al 2002) Takano (1976;1979), Rivera (1981), Hallegraeff (1984), Licea (1992), Hernández-Becerril et al (1995), Aké-Castilho et al (1999), Sar et al (2002), Fryxell & Hasle (2003).…”
Section: Th Alassiosira Minusculamentioning
confidence: 99%
“…Round and Mann (1980) observed the fine structure of rota, which has several spokes per areola and no slits. In all Rhaphoneidaceae genera, rotae always have two spokes per areola and no fin-like projections with or without slit (Andrews & Rivera 1987, Blazé 1984, Louvrou et al 2012, Round et al 1990, Sar et al 2007, Takano 1982. Thus, it is suggested that the number of spokes and the pairs of fin-like projections are taxonomically important characters for separating the family Psammodiscaceae from Rhaphoneidaceae.…”
Section: Discussionmentioning
confidence: 99%
“…2017 IntroductIon Taxa belonging to the genus Thalassiosira Cleve emend. Hasle (1973) from Argentinian coastal waters were previously studied including ultrastructural analysis by Lange et al (1983), Sar & Ferrario (1987), Ferrario & Sar (1988), Gayoso (1989), Sar (1996), Sar et al (2001Sar et al ( , 2002Sar et al ( , 2011, Sunesen & Sar (2004) and Sunesen (2007), nevertheless, nanoplanktonic species were frequently overlooked.…”
mentioning
confidence: 99%